Indonesia’s Intangibles Transfer Pricing Regime: An International Comparative Review - Yusuf Akhmadi (Directorate General of Taxes, 2025)
Intangibles are central to the digital economy, generating significant market value and premium returns. In the pre-BEPS era, intangibles facilitated tax avoidance through profit shifting to tax havens. The post-BEPS era emphasizes intangible profit allocation based on economic ownership, contributions to DEMPE functions, and the assumption of significant economic risks. As an emerging global economy, Indonesia faces challenges in transfer pricing for intangibles and must adapt to international guidelines and reforms. Using a qualitative comparative legal method, this study compares Indonesia’s transfer pricing regime for intangibles with the OECD Transfer Pricing Guidelines, the UN Transfer Pricing Manual, and the domestic laws of the US, UK, and China. The analysis focuses on identification, analytical frameworks, income attribution, transfer pricing methods, and special considerations. Indonesia’s regime generally aligns with international best practices, offering robust guidance and frameworks. However, the regime lacks guidance on local intangibles identification, income attribution, and the provision of hard-to-value intangibles. Indonesia can further enhance its intangibles regime by adopting certain approaches from the surveyed jurisdictions.